CD4(+) T-cell counts and plasma HIV-1 RNA levels beyond 5 years of highly active antiretroviral therapy (HAART) - Li, Xiuhong (2011)
BACKGROUND: The heterogeneity of CD4(+) T-cell counts and HIV-1 RNA at 5-12 years after the initiation of highly active antiretroviral therapy (HAART) remains largely uncharacterized. METHODS: In the Multicenter AIDS Cohort Study, 614 men who initiated HAART contributed data 5-12 years subsequently. Multivariate regression was used to evaluate the predictors of CD4(+) counts and HIV-1 RNA levels. RESULTS: At 5-12 years post-HAART, the median CD4(+) T-cell count was 586 (inter quartile range (IQR): 421-791) cells/μl and 78% of the HIV-1 RNA measurements were undetectable. Higher CD4(+) T-cell counts 5-12 years post-HAART were predicted by higher CD4(+) T-cell counts and higher total lymphocyte count pre-HAART, lack of hepatitis B or C virus co-infections, and greater CD4(+) T-cell change as well as suppressed HIV-1 RNA in the first 5 years after starting HAART. Older men (≥50 years) with 351-500 CD4(+) cells/μl at HAART initiation had adjusted mean CD4(+) T-cell count of 643 cells/μl at 10-12 years post-HAART, which was similar to the adjusted mean CD4(+) T-cell count (670 cells/μl, p=0.45) in this period for younger men starting HAART with lower CD4(+) T-cell counts. HIV-1 RNA suppression in the first 5 years post-HAART predicted subsequent viral suppression. CONCLUSION: Immunological and virological responses in the first five years post-HAART predicted subsequent CD4(+) T-cell counts and HIV-1 RNA levels. The association between age and subsequent CD4(+) T-cell count supports incorporating age in guidelines for use of HAART.